Концепція створення комплексного музею під відкритим небом на основі Підгорецько-пліснеських територій - Ремешило-Рибчинська, О.; Брич, М.; Remeshylo-Rybchynska, O.; Brych, M. (Видавництво Львівської політехніки, 2019)
Запропоновано ідею створення музею під відкритим небом, що поєднав би два пам’яткові об’єкти – архітектурний ансамбль та археологічний заповідник в один великий комплекс. Описано пропозицію формування архітектурного простору, що охоплює навколишнє середовище. Проаналізовано позитивні та проблемні аспекти створення музею. Розглянуто особливості створення великого музею, що поєднує різнорідні пам’ятки, розташовані поруч.

Ukraine has a huge historical and cultural potential. Unfortunately, their usage is ineffective. State support for museums is limited, therefore the problem of developing programs for their creation, maintenance and activity arises accordingly. New approaches to exhibiting are changing the approach to the architectural and spatial organization of the museum. Remaining an educational institution, the museum attracts a large mass of the population, becomes a large cultural and educational center, where the museum function becomes only one of many parts of the general program. The basis of this article are works that reflect the importance of the environment and the historical context of the sites. Among them are the studies of V. Vechersky, M. Bevz, O. Lesyk, L. Pribieha, E. Mikhailovsky, M. Maistrovskaya, V. Ievleva, O. Popelnitsky, O. Serdyuk. The theme of open-air museums based on immovable monuments creating develop previous research by the authors, O. Remesilo-Rybchynska and M. Brych. The purpose of the article is to demonstrate the possibilities of complex open-air museums, which unites the various monuments located nearby, on the example of the Plisnesk archeological complex and the Pidgoretsky Castle ensemble. The open-air museum forms a meaningful environment, offering visitors instead of the role of a passive spectator to participate in the production of new meanings and cultural objects, to acquire new information, knowledge, and skills. If the two monuments are located nearby, it can raise the popularity of both, as well as make it easier and more cost-effective to arrange service facilities that will unite two museums in one institution. Open-air museums have more possibilities because they include not only individual architectural monuments, but also an environment that is more adaptable to the needs of the museum. The creation of an open-air museum on the basis of the Pidhirtsi and Plisnesk Heritage Complex is of great economic and cultural importance to the village community as well as to the district as a whole. It is difficult to overestimate the cultural and educational potential of the complex open-air museum on the basis of the Pidhirtsi architectural ensemble and the Plisnesk archeological reserve.
The concept of a complex open air museum creation based on the territories of pidhirtsi and plisnesk
Keywords: музей під відкритим небом; пам’ятка архітектури; пам’ятка археології; музеєфікація; open-air museum; monument of architecture; monument of archaeology; museumfication; (719; 902); 069